Daily almond consumption in cardiovascular disease prevention via LDL-C change in the U.S. population: a cost-effectiveness analysis - Jifan Wang; Michelle A. Lee Bravatti; Elizabeth J. Johnson; Gowri Raman (BMC, 2020)
Abstract Background Heart disease is the leading cause of death in the United States. The U.S. Food and Drug Administration approved the health claim that 1.5 oz (42.5 g) of nut intake may reduce the risk of cardiovascular disease. Previous studies have focused on the cost-effectiveness of other foods or dietary factors on primary cardiovascular disease prevention, yet not in almond consumption. This study aimed to examine the cost-effectiveness of almond consumption in cardiovascular disease primary prevention. Perspective & Setting This study assessed the cost-effectiveness of consuming 42.5 g of almond from the U.S. healthcare sector perspective. Methods A decision model was developed for 42.5 g of almond per day versus no almond consumption and cardiovascular disease in the U.S. population. Parameters in the model were derived from the literature, which included the probabilities of increasing low-density lipoprotein cholesterol, developing acute myocardial infarction and stroke, treating acute myocardial infarction, dying from the disease and surgery, as well as the costs of the disease and procedures in the U.S. population, and the quality-adjusted life years. The cost of almonds was based on the current price in the U.S. market. Sensitivity analyses were conducted for different levels of willingness-to-pay, the probabilistic sensitivity analysis, ten-year risk prevention, different costs of procedures and almond prices, and patients with or without cardiovascular disease. Results The almond strategy had $363 lower cost and 0.02 higher quality-adjusted life years gain compared to the non-almond strategy in the base-case model. The annual net monetary benefit of almond consumption was $1421 higher per person than no almond consumption, when the willingness to pay threshold was set at $50,000 for annual health care expenditure. Almond was more cost-effective than non-almond in cardiovascular disease prevention in all the sensitivity analyses. Conclusion Consuming 42.5 g of almonds per day is a cost-effective approach to prevent cardiovascular disease in the short term and potentially in the long term.